Building the infrastructure for cloud security a solutions view - Yeluri, Raghu; Castro-Leon, Enrique (Apress, 2014)
The goal of the book is to gather together all the relevant security technologies for servers and clients and show through case studies (from the Intel Cloud Builder efforts) how the technologies can work together to provide a strong end-to-end Cloud Security Infrastructure. This book provides a comprehensive look at the various facets of Cloud Security; infrastructure, network, services, Compliance and users. It will provide real world case studies to articulate the real and perceived risks and challenges in deploying and managing services in a cloud infrastructure from a Security perspective.
Includes bibliographical references and index. - Online resource; title from PDF title page (SpringerLink, viewed March 31, 2014)
Keywords: Cloud computing -- Security measures; Data encryption (Computer science); computerwetenschappen; computer sciences; gegevensbeheer; data management; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen); Infonuagique; Sécurité; Mesures; Chiffrement (Informatique); Computer science